1984
DOI: 10.1111/j.1469-1809.1984.tb01016.x
|View full text |Cite
|
Sign up to set email alerts
|

β‐Adrenoceptor binding defects in cell lines from families with manic‐depressive disorder

Abstract: Binding of 125I-iodohydroxybenzylpindolol to beta-adrenoceptors has been examined in lymphoblastoid cell lines from members of 5 families affected by manic-depressive disorder. Cell lines from 6 manic-depressives, 7 unaffected relatives and 11 non-psychiatric controls were examined. Binding was reduced to less than half of control values in cell lines from 4 out of 6 manic-depressives and only 1 out of 18 unaffected relatives or controls. All the cell lines with reduced beta-adrenoceptor binding came from 3 fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
14
1

Year Published

1984
1984
2009
2009

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(18 citation statements)
references
References 49 publications
3
14
1
Order By: Relevance
“…A particularly salient question is whether high basal Ca 2+ concentration in platelets and/or lymphocytes from subjects with bipolar disorder is state dependent and normalizes with improvement in mood, as suggested by some studies (8,10), or trait dependent and persistently high in euythmia, as supported by observations of others (11,12). The notion that trait-related abnormalities in cellular responses occur in bipolar disorder is also supported by findings from studies of other cellular properties, i.e., differences in β-adrenoceptor density and functionality (13,14) and in Na + -, K + -ATPase activities in transformed lymphoblasts (15) between patients with bipolar disorder and healthy subjects.…”
supporting
confidence: 58%
See 1 more Smart Citation
“…A particularly salient question is whether high basal Ca 2+ concentration in platelets and/or lymphocytes from subjects with bipolar disorder is state dependent and normalizes with improvement in mood, as suggested by some studies (8,10), or trait dependent and persistently high in euythmia, as supported by observations of others (11,12). The notion that trait-related abnormalities in cellular responses occur in bipolar disorder is also supported by findings from studies of other cellular properties, i.e., differences in β-adrenoceptor density and functionality (13,14) and in Na + -, K + -ATPase activities in transformed lymphoblasts (15) between patients with bipolar disorder and healthy subjects.…”
supporting
confidence: 58%
“…The noted abnormalities in membrane receptors and cellular responses in transformed lymphoblasts from subjects with bipolar disorder (13,14) suggest that this cell model might be useful for establishing more directly whether abnormal Ca 2+ homeostasis in bipolar disorder is trait related. Accordingly, in the present study we compared basal Ca 2+ levels in Epstein-Barr-virus-immortalized B lymphoblasts and freshly isolated T lymphocytes from patients with bipolar I disorder, bipolar II disorder, or major depression with those from a mixed group of psychiatric patients with nonmood disorders and a healthy comparison cohort.…”
mentioning
confidence: 99%
“…In addition, it has repeatedly demonstrated trait-dependent defects in signal transduction of BAD either in cAMP or in Ca 2 þ signaling (Kay et al, 1994;Wright et al, 1984;Shamir et al, 1998;Emamghoreishi et al, 2000). It offers an advantage over the blood platelet as neurohormonal and medication influences were removed by several passages in cell culture.…”
Section: Introductionmentioning
confidence: 99%
“…Due to inaccessibility to the human brain, a peripheral cell model, the EBV-transformed lymphoblast, which presents several advantages, has been used in BAD studies (Wright et al, 1984;Kay et al, 1994;Shamir et al, 1998;Emamghoreishi et al, 2000): this cell, easy to culture, expresses BDNF protein and its cognate receptor, TrkB (Schenone et al, 1996). In addition, it has repeatedly demonstrated trait-dependent defects in signal transduction of BAD either in cAMP or in Ca 2 þ signaling (Kay et al, 1994;Wright et al, 1984;Shamir et al, 1998;Emamghoreishi et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, for biological psychiatry in general the potential benefits of concentrating on pairs of relatives (Reider & Gershon, 1978) or on multiple classes of relatives (Cloninger et al 1981) are large and are only just beginning to be exploited. One interesting recent example is the study of Wright et al (1984), which demonstrated decreased /ff-adrenoreceptors on lymphoblastoid cells in the ill members of three families affected by manicdepressive psychosis, but not among healthy relatives. In two other families the finding was absent in both ill and healthy individuals.…”
mentioning
confidence: 99%